Technology transfer of beef cattle raising for productivity improvement based on intensive farming of beef cattle raising group in Pua District, Nan Province - Prapatigul, P.; Sreshthaputra, S. (International Journal of Agricultural Technology, 2021)
Beef cattle have been found to be a significant part of the Thai farmers’ lifestyle since ancient times. Knowledge and methods of beef cattle raising were accumulated and passed on from generation to generation until it led to the raising of beef cattle with basic farming management that does not comply with the present principles. The results indicated that the majority of the farmers lack knowledge about beef cattle raising in accordance with the intensive farming practice. Consequently, farmers were required to participate in a one-day training workshop during the month of May 2017. Comparing the knowledge of farmers before and after concerning the technology transfer, the study found that farmers have acquired more knowledge and they would apply the knowledge gained from the training and adapted it for raising beef cattle at the highest level in their own way. The study also found that related departments should assess the readiness of farmers before promoting beef cattle farming based on intensive farming practice. The intensive farming practice included readiness of the farmers, physical and biological readiness among the community, and readiness of market receiving the product should correspondingly be implemented gradually along with the establishment of Learning Network and Business Network among farmers